A versatile ex vivo technique for assaying tumor angiogenesis and microglia in the brain - Ghoochani, Ali; Yakubov, Eduard; Sehm, Tina; Fan, Zheng; Hock, Stefan; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai E. (Oncotarget, 2016)
Primary brain tumors are hallmarked for their destructive activity on the microenvironment and vasculature. However, solely few experimental techniques exist to access the tumor microenvironment under anatomical intact conditions with remaining cellular and extracellular composition. Here, we detail an ex vivo vascular glioma impact method (VOGIM) to investigate the influence of gliomas and chemotherapeutics on the tumor microenvironment and angiogenesis under conditions that closely resemble the in vivo situation. We generated organotypic brain slice cultures from rats and transgenic mice and implanted glioma cells expressing fluorescent reporter proteins. In the VOGIM, tumor-induced vessels presented the whole range of vascular pathologies and tumor zones as found in human primary brain tumor specimens. In contrast, non-transformed cells such as primary astrocytes do not alter the vessel architecture. Vascular characteristics with vessel branching, junctions and vessel meshes are quantitatively assessable as well as the peritumoral zone. In particular, the VOGIM resembles the brain tumor microenvironment with alterations of neurons, microglia and cell survival. Hence, this method allows live cell monitoring of virtually any fluorescence-reporter expressing cell. We further analyzed the vasculature and microglia under the influence of tumor cells and chemotherapeutics such as Temozolamide (Temodal/Temcad®). Noteworthy, temozolomide normalized vasculare junctions and branches as well as microglial distribution in tumor-implanted brains. Moreover, VOGIM can be facilitated for implementing the 3Rs in experimentations. In summary, the VOGIM represents a versatile and robust technique which allows the assessment of the brain tumor microenvironment with parameters such as angiogenesis, neuronal cell death and microglial activity at the morphological and quantitative level.
EVALuna2:22857

Cabazitaxel operates anti-metastatic and cytotoxic via apoptosis induction and stalls brain tumor angiogenesis - Ghoochani, Ali; Hatipoglu Majernik, Gökce; Sehm, Tina; Wach, Sven; Buchfelder, Michael; Taubert, Helge; Eyupoglu, Ilker Y.; Savaskan, Nicolai (Oncotarget, 2016)
Taxanes target microtubules and are clinically established chemotherapeutic agents with proven efficacy in human cancers. Cabazitaxel (XRP-6258, Jevtana®) is a second generation semisynthetic taxane with high chemotherapeutic potential in prostate cancer. There, cabazitaxel can overcome docetaxel-resistant prostate cancer. Here, we tested the effects of cabazitaxel on glioma cells, and non-transformed cells such as neurons and astrocytes. Cabazitaxel operates highly toxic in various human glioma cells at nanomolar concentrations. In contrast, primary astrocytes and neurons are not affected by this agent. Cabazitaxel disrupts cytoskeletal F-actin fibers and induces apoptotic cell death in gliomas. Moreover, cabazitaxel displayed highest efficacy in inhibiting glioma cell migration and invasion. Here we demonstrate that cabazitaxel inhibited tumor migration already at 1 nM. We also tested cabazitaxel in the ex vivo VOGiM assay. Cabazitaxel stalled glioma growth and at the same time inhibited tumor-induced angiogenesis. In summary, we found that cabazitaxel operates as an apoptosis-inducing gliomatoxic agent with strongest effects on migration and invasive growth. Thus, our report uncovered cabazitaxel actions on gliomas and on the brain tumor microenvironment. These data reveal novel aspects for adjuvant approaches when applied to brain tumor patients.
EVALuna2:33569

Cytotoxic profiling of artesunic and betulinic acids and their synthetic hybrid compound on neurons and gliomas - Ackermann, Annemarie; Capci Karagöz, Aysun; Ghoochani, Ali; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Tsogoeva, Svetlana; Savaskan, Nicolai (Oncotarget, 2017)
Gliomas are brain-born tumors with devastating impact on their brain microenvironment. Novel approaches employ multiple combinations of chemical compounds in synthetic hybrid molecules to target malignant tumors. Here, we report on the chemical hybridization approach exemplified by artesunic acid (ARTA) and naturally occurring triterpene betulinic acid (BETA). Artemisinin derived semisynthetic compound artesunic acid (ARTA) and naturally occurring triterpene BETA were used to synthetically couple to the hybrid compound termed 212A. We investigated the impact of 212A and its parent compounds on glioma cells, astrocytes and neurons. ARTA and BETA showed cytotoxic effects on glioma cells at micromolar concentrations. ARTA was more effective on rodent glioma cells compared to BETA, whereas BETA exhibited higher toxic effects on human glioma cells compared to ARTA. We investigated these compounds on non-transformed glial cells and neurons as well. Noteworthy, ARTA showed almost no toxic effects on astrocytes and neurons, whereas BETA as well as 212A displayed neurotoxicity at higher concentrations. Hence we compared the efficacy of the hybrid 212A with the combinational treatment of its parent compounds ARTA and BETA. The hybrid 212A was efficient in killing glioma cells compared to single compound treatment strategies. Moreover, ARTA and the hybrid 212A displayed a significant cytotoxic impact on glioma cell migration. Taken together, these results demonstrate that both plant derived compounds ARTA and BETA operate gliomatoxic with minor neurotoxic side effects. Altogether, our proof-of-principle study demonstrates that the chemical hybrid synthesis is a valid approach for generating efficacious anti-cancer drugs out of virtually any given structure. Thus, synthetic hybrid therapeutics emerge as an innovative field for new chemotherapeutic developments with low neurotoxic profile.
EVALuna2:102197

MCT4 Promotes Tumor Malignancy in F98 Glioma Cells - Reuß, Anna Maria; Groos, Dominik; Ghoochani, Ali; Buchfelder, Michael; Savaskan, Nicolai (Journal of Oncology, 2021)
Monocarboxylate transporter 4 (MCT4, SLC16A3) is elevated under hypoxic conditions in many malignant tumors including gliomas. Moreover, MCT4 expression is associated with shorter overall survival. However, the functional consequences of MCT4 expression on the distinct hallmarks of cancer have not yet been explored at the cellular level. Here, we investigated the impact of MCT4 overexpression on proliferation, survival, cell death, migration, invasion, and angiogenesis in F98 glioma cells. Stable F98 glioma cell lines with MCT4 overexpression, normal expression, and knockdown were generated. Distinct hallmarks of cancer were examined using in silico analysis, various in vitro cell culture assays, and ex vivo organotypic rat brain slice culture model. Consistent with its function as lactate and proton exporter, MCT4 expression levels correlated inversely with extracellular pH and proportionally with extracellular lactate concentrations. Our results further indicate that MCT4 promotes proliferation and survival by altered cell cycle regulation and cell death mechanisms. Moreover, MCT4 overexpression enhances cell migration and invasiveness via reorganization of the actin cytoskeleton. Finally, MCT4 inhibition mitigates the induction of angiogenesis, suggesting that MCT4 also plays a crucial role in tumor-related angiogenesis. In summary, our data highlight MCT4/SLC16A3 as a key gene for distinct hallmarks of tumor malignancy in glioma cells.
CRIS-Team Scopus Importer:2021-05-14

MIF-CD74 signaling impedes microglial M1 polarization and facilitates brain tumorigenesis - Ghoochani, Ali; Schwarz, Martin; Yakubov, Eduard; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; Bucala, R.; Savaskan, N. E.; Eyupoglu, I. Y. (Oncogene, 2016)
Microglial cells in the brain tumor microenvironment are associated with enhanced glioma malignancy. They persist in an immunosuppressive M2 state at the peritumoral site and promote the growth of gliomas. Here, we investigated the underlying factors contributing to the abolished immune surveillance. We show that brain tumors escape pro-inflammatory M1 conversion of microglia via CD74 activation through the secretion of the cytokine macrophage migration inhibitory factor (MIF), which results in a M2 shift of microglial cells. Interruption of this glioma-microglial interaction through an antibody-neutralizing approach or small interfering RNA (siRNA)-mediated inhibition prolongs survival time in glioma-implanted mice by reinstating the microglial pro-inflammatory M1 function. We show that MIF-CD74 signaling inhibits interferon (IFN)-γ secretion in microglia through phosphorylation of microglial ERK1/2 (extracellular signal-regulated protein kinases 1 and 2). The inhibition of MIF signaling or its receptor CD74 promotes IFN-γ release and amplifies tumor death either through pharmacological inhibition or through siRNA-mediated knockdown. The reinstated IFN-γ secretion leads both to direct inhibition of glioma growth as well as inducing a M2 to M1 shift in glioma-associated microglia. Our data reveal that interference with the MIF signaling pathway represents a viable therapeutic option for the restoration of IFN-γ-driven immune surveillance.
EVALuna2:33151

Plasticity Related Gene 3 (PRG3) overcomes myelin-associated growth inhibition and promotes functional recovery after spinal cord injury - Broggini, Thomas; Schnell, Lisa; Ghoochani, Ali; Mateos, Jose Maria; Buchfelder, Michael; Wiendieck, Kurt; Schaefer, Michael K.; Eyupoglu, Ilker Y.; Savaskan, Nicolai E. (Aging-Us, 2016)
The Plasticity Related Gene family covers five, brain-specific, transmembrane proteins (PRG1-5, also termed LPPR1-5) that operate in neuronal plasticity during development, aging and brain trauma. Here we investigated the role of the PRG family on axonal and filopodia outgrowth. Comparative analysis revealed the strongest outgrowth induced by PRG3 (LPPR1). During development, PRG3 is ubiquitously located at the tip of neuronal processes and at the plasma membrane and declines with age. In utero electroporation of PRG3 induced dendritic protrusions and accelerated spine formations in cortical pyramidal neurons. The neurite growth promoting activity of PRG3 requires RasGRF1 (RasGEF1/Cdc25) mediated downstream signaling. Moreover, in axon collapse assays, PRG3-induced neurites resisted growth inhibitors such as myelin, Nogo-A (Reticulon/RTN-4), thrombin and LPA and impeded the RhoA-Rock-PIP5K induced neurite repulsion. Transgenic adult mice with constitutive PRG3 expression displayed strong axonal sprouting distal to a spinal cord lesion. Moreover, fostered PRG3 expression promoted complex motor-behavioral recovery compared to wild type controls as revealed in the Schnell swim test (SST). Thus, PRG3 emerges as a developmental RasGRF1-dependent conductor of filopodia formation and axonal growth enhancer. PRG3-induced neurites resist brain injury-associated outgrowth inhibitors and contribute to functional recovery after spinal cord lesions. Here, we provide evidence that PRG3 operates as an essential neuronal growth promoter in the nervous system. Maintaining PRG3 expression in aging brain may turn back the developmental clock for neuronal regeneration and plasticity.
EVALuna2:33854

Sulfasalazine impacts on ferroptotic cell death and alleviates the tumor microenvironment and glioma-induced brain edema. - Sehm, Tina; Fan, Zheng; Ghoochani, Ali; Rauh, Manfred; Engelhorn, Tobias; Minakaki, Georgia; Dörfler, Arnd; Klucken, Jochen; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai (Oncotarget, 2016)
The glutamate transporter xCT (SCL7a11, system Xc-, SXC) is an emerging key player in glutamate/cysteine/glutathione homeostasis in the brain and in cancer. xCT expression correlates with the grade of malignancy. Here, we report on the use of the U.S. Food and Drug Administration and EMA-approved xCT inhibitor, sulfasalazine (SAS) in gliomas. SAS does not affect cell viability in gliomas at concentrations below 200 µM. At higher concentrations SAS becomes gliomatoxic. Mechanistically SAS inhibits xCT and induces ferroptotic cell death in glioma cells. There is no evidence for impact on autophagic flux following SAS application. However, SAS can potentiate the efficacy of the standard chemotherapeutic and autophagy-inducing agent temozolomide (Temcat, Temodal or Temodar®). We also investigated SAS in non-transformed cellular constituents of the brain. Neurons and brain tissue are almost non-responding to SAS whereas isolated astrocytes are less sensitive towards SAS toxicity compared to gliomas. In vivo SAS treatment does not affect experimental tumor growth and treated animals revealed comparable tumor volume as untreated controls. However, SAS treatment resulted in reduced glioma-derived edema and, hence, total tumor volume burden as revealed by T2-weighted magnetic resonance imaging. Altogether, we show that SAS can be utilized for targeting the glutamate antiporter xCT activity as a tumor microenvironment-normalizing drug, while crucial cytotoxic effects in brain tumors are minor.

Sunitinib impedes brain tumor progression and reduces tumor-induced neurodegeneration in the microenvironment - Hatipoglu, Gökce; Hock, Stefan; Weiss, Ruth; Fan, Zheng; Sehm, Tina; Ghoochani, Ali; Buchfelder, Michael; Savaskan, Nicolai E.; Eyüpoglu, Ilker Yasin (Cancer Science, 2015)
Malignant gliomas can be counted to the most devastating tumors in humans. Novel therapies do not achieve significant prolonged survival rates. The cancer cells have an impact on the surrounding vital tissue and form tumor zones, which make up the tumor microenvironment. We investigated the effects of sunitinib, a small molecule multitargeted receptor tyrosine kinase inhibitor, on constituents of the tumor microenvironment such as gliomas, astrocytes, endothelial cells, and neurons. Sunitinib has a known anti-angiogenic effect. We found that sunitinib normalizes the aberrant tumor-derived vasculature and reduces tumor vessel pathologies (i.e. auto-loops). Sunitinib has only minor effects on the normal, physiological, non-proliferating vasculature. We found that neurons and astrocytes are protected by sunitinib against glutamate-induced cell death, whereas sunitinib acts as a toxin towards proliferating endothelial cells and tumor vessels. Moreover, sunitinib is effective in inducing glioma cell death. We determined the underlying pathways by which sunitinib operates as a toxin on gliomas and found vascular endothelial growth factor receptor 2 (VEGFR2, KDR/Flk1) as the main target to execute gliomatoxicity. The apoptosis-inducing effect of sunitinib can be mimicked by inhibition of VEGFR2. Knockdown of VEGFR2 can, in part, foster the resistance of glioma cells to receptor tyrosine kinase inhibitors. Furthermore, sunitinib alleviates tumor-induced neurodegeneration. Hence, we tested whether temozolomide treatment could be potentiated by sunitinib application. Here we show that sunitinib can amplify the effects of temozolomide in glioma cells. Thus, our data indicate that combined treatment with temozolomide does not abrogate the effects of sunitinib. In conclusion, we found that sunitinib acts as a gliomatoxic agent and at the same time carries out neuroprotective effects, reducing tumor-induced neurodegeneration. Thus, this report uncovered sunitinib's actions on the brain tumor microenvironment, revealing novel aspects for adjuvant approaches and new clinical assessment criteria when applied to brain tumor patients.
EVALuna2:22836